An Exploratory Study of Four Urban Community Libraries in Nampula City, Mozambique: Do They Satisfy Community Informational Needs? - Szabo, Elizabeth Eva; Vieira, Ilidia (Libri, 2017)
This exploratory study describes the characteristics of four independent urban community libraries in Nampula city, located in northern Mozambique, East Africa. In a country where public library services are inadequately equipped to address the educational, informational and cultural needs of its citizens, the emergence of urban community libraries in the city indicates that the population is seeking better alternative sources of information. The study profiles four urban libraries to identify their role in the communities they serve and determine whether they conform to Mostert’s (1998) community library model. A case-study design was used with data collection techniques of structured interviews to collect qualitative data from library directors and librarians, a multiple choice questionnaire to obtain user responses, while further statistical data was obtained from collection, circulation and library user records. Findings indicate these four urban libraries only minimally adhere to Mostert’s model and are instead mimicking existing public and school libraries by catering to predominantly secondary and university level students. As a result, the educational, informational and cultural needs of other key groups in the community, such as the illiterate, neo-literate and disadvantaged, are ignored. This is due to a lack of trained library professionals and restrictive library policies.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; access to services / acesso a serviços; education / educação

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde